A descriptive analysis of non-Cochrane child-relevant systematic reviews published in 2014 - Gates, Michelle; Elliott, Sarah A.; Johnson, Cydney; Thomson, Denise; Williams, Katrina; Fernandes, Ricardo M.; Hartling, Lisa (BMC Medical Research Methodology, 2018)
Consumers, clinicians, policymakers and researchers require high quality evidence to guide decision-making in child health. Though Cochrane systematic reviews (SRs) are a well-established source of evidence, little is known about the characteristics of non-Cochrane child-relevant SRs. To complement published descriptions of Cochrane SRs, we aimed to characterize the epidemiologic, methodological, and reporting qualities of non-Cochrane child-relevant SRs published in 2014.